The Role of Liver Biopsy in Detection of Hepatic Oxidative Stress - Mahmoud Rushdi Abd Ellah (Veterinary Medicine International)
The goal of the current paper is to explore the role of liver biopsy as a tool in detection of hepatic oxidative stress, with brief notes on different types of free radicals, antioxidants, hepatic and blood oxidative stress, and lipid peroxidation. Hepatic oxidative stress was investigated for many years in human and animals, but most of the studies performed in animals were concerned with studying oxidative status in the liver tissues after slaughtering or euthanasia. However, in human medicine, a large number of studies were implemented to investigate the status of antioxidants in liver biopsy specimens. Similar studies are required in animals, as the changes in hepatic antioxidants and formation of lipid peroxide give a good idea about the condition of the liver. On the other hand, hepatic disease may present without significant effect on blood oxidative status, and, consequently, the best way to detect the status of hepatic oxidants and antioxidants is through measuring in liver biopsy. Measuring antioxidants status directly in the liver tissues gives an accurate estimation about the condition of the liver, permits the diagnosis of hepatic dysfunction, and helps to determine the degree of deterioration in the hepatic cells.